Measurement of maternal functioning during pregnancy and postpartum: findings from the cross-sectional WHO pilot study in Jamaica, Kenya, and Malawi - Jenny A. Cresswell; Kelli D. Barbour; Doris Chou; Affette McCaw-Binns; Veronique Filippi; Jose Guilherme Cecatti; Maria Barreix; Max Petzold; Nenad Kostanjsek; Sara Cottler-Casanova; Lale Say (BMC, 2020)
Abstract Background The World Health Organization's definition of maternal morbidity refers to "a negative impact on the woman's wellbeing and/or functioning". Many studies have documented the, mostly negative, effects of maternal ill-health on functioning. Although conceptually important, measurement of functioning remains underdeveloped, and the best way to measure functioning in pregnant and postpartum populations is unknown. Methods A cross-sectional study among women presenting for antenatal (N = 750) and postpartum (N = 740) care in Jamaica, Kenya and Malawi took place in 2015-2016. Functioning was measured through the World Health Organization Disability Assessment Schedule (WHODAS-12). Data on health conditions and socio-demographic characteristics were collected through structured interview, medical record review, and clinical examination. This paper presents descriptive data on the distribution of functioning status among pregnant and postpartum women and examines the relationship between functioning and health conditions. Results Women attending antenatal care had a lower level of functioning than those attending postpartum care. Women with a health condition or associated demographic risk factor were more likely to have a lower level of functioning than those with no health condition. However, the absolute difference in functioning scores typically remained modest. Conclusions Functioning is an important concept which integrates a woman-centered approach to examining how a health condition affects her life, and ultimately her return to functioning after delivery. However, the WHODAS-12 may not be the optimal tool for use in this population and additional components to capture pregnancy-specific issues may be needed. Challenges remain in how to integrate functioning outcomes into routine maternal healthcare at-scale and across diverse settings.